Pengaruh Pemberian Punishment terhadap Motivasi Belajar Peserta Didik Kelas V di SDN 1 Selebung Ketangga Tahun Pelajaran 2020/2021 - Purwanto, Rudi; Hadi, Muhammad Irwan (Lembaga Yasin AlSys, 2021)
This research is Ex-postfacto research, namely research that examines the relationship between cause and effect. The purpose of this study was to determine whether the provision of punishment had an effect on the learning motivation of fifth grade students at SDN 1 Selebung Ketangga. The data collection methods used in this study were questionnaires, observations, and documentation. The results showed that X2 (Punishment) had an effect on Y (learning motivation).